THE ROLE OF INFORMING PATIENTS ABOUT HYPERTENSION IN POLYCLINIC SETTINGS - Shakhzada S. Gulyamova; Kholida Kh. Khalimova (Web of Journals Publishing, 2025)
A retrospective analysis (over the last five years) was carried out on 222 randomly selected outpatient records from among patients undergoing dispensary observation with arterial hypertension in family clinics (n=54) and in a number of rural family clinics of the Republic of Uzbekistan (n=168). Data from a retrospective analysis of outpatient records were compared with the results of examination of patients (questioning, examination, anthropometry, blood pressure measurement, cholesterol determination, etc.). Doctors from family clinics in Tashkent and rural family clinics in the regions of the Republic were interviewed. Before training, 156 doctors were surveyed, after training 119, and 236 patients undergoing follow-up with hypertension were surveyed and examined. Subsequently, some of them (n=122, main group) completed an awareness course at a health school, and some (n=114, comparison group) did not participate in the educational program. All patients were monitored for 2 years with subsequent re-examination and examination.
Keywords: Arterial hypertension, risk factors, family clinic, awareness, prevention of hypertension.